PERSEPSI MASYARAKAT TERHADAP PROGRAM VAKSINASI COVID-19 DI WILAYAH DESA SARAKAN RT 002 RW 002 KECAMATAN SEPATAN KABUPATEN TANGERANG BANTEN - Rina Puspita Sari; Sulaeman; Siti Suhaimah (Nusantara Hasana Journal, 2023)
Public perception of the Covid-19 vaccine is a response or acceptance of the information processed regarding the design of the halalness of the vaccine, the willingness to be vaccinated and the capacity of health workers who provide the covid-19 vaccine. This is because there are so many issues that affect information about the Covid-19 vaccine. The purpose of this study aims to determine the public's perception of the Covid-19 vaccine in Sarakan Village Rt 002 Rw 002. This study uses a qualitative research design with a phenomenological approach. In-depth interviews were conducted with 8 people from Sarakan Village Rt 002 Rw 002 regarding perceptions about the Covid-19 vaccine. Furthermore, the results of the interview were processed using the Colaizzi technique. This study produced six main themes, namely (1) Public knowledge about Covid-19 vaccination, (2) Community family support about Covid-19 vaccination, (3) Patterns due to the Covid-19 vaccination program, (4) Identification of participant characteristics and location sources, (5) Sources of community obstacles to the Covid- 19 vaccination program, and (6) Hopes of the sarakan village community Rt 002 Rw 002 after the Covid-19 vaccination program. The results of the study show that knowledge affects the public's perception of the covid-19 vaccine, therefore it is necessary to provide information in a comprehensive and equitable manner to all people about the usefulness, safety of the covid-19 vaccine and all updated information about the covid-19 vaccine.